Better than expected or as bad as you thought? The neurocognitive development of probabilistic feedback processing - Van Den Bos, Wouter; Güroğlu, Berna; Van Den Bulk, Bianca G.; Rombouts, Serge A.; Crone, Eveline A. (Frontiers in Human Neuroscience, 2009)
Learning from feedback lies at the foundation of adaptive behavior. Two prior neuroimaging studies have suggested that there are qualitative differences in how children and adults use feedback by demonstrating that dorsolateral prefrontal cortex (DLPFC) and parietal cortex were more active after negative feedback for adults, but after positive feedback for children. In the current study we used functional magnetic resonance imaging (fMRI) to test whether this difference is related to valence or informative value of the feedback by examining neural responses to negative and positive feedback while applying probabilistic rules. In total, 67 healthy volunteers between ages 8 and 22 participated in the study (8-11-years, n=18; 13-16-years, n=27; 18-22-years, n=22). Behavioral comparisons showed that all participants were able to learn probabilistic rules equally well. DLPFC and dorsal anterior cingulate cortex were more active in younger children following positive feedback and in adults following negative feedback, but only when exploring alternative rules, not when applying the most advantageous rules. These findings suggest that developmental differences in neural responses to feedback are not related to valence per se, but that there is an age-related change in processing learning signals with different informative value